Legal Protection for the Owner of Brand Rights According to Law Number 20 / 2016 of Trademark and Geographical Indication (Trademark And Geographical Indication) - Nahdliyah, Hadziqotun; Khitam, Muhammad Chusnul; Fitri, Rika Izatul (Jurnal Independent, 2025)
ABSTRACT According to Law Number 20 of 2016 concerning Trademarks and Geographical Indications, brand owners must register their brands with the Directorate General of Intellectual Property in order to maintain healthy, fair business competition and obtain legal protection. Based on the background above, the author proposes a problem formulation, namely how is the legal protection for brand rights holders according to Law Number 20 of 2016 concerning Trademarks and Geographical Indications? This research method uses a normative legal research type, with a statute approach. The legal materials used are primary legal materials which include: Law Number 20 of 2016 concerning Trademarks and Geographical Indications and Law Number 8 of 1999 concerning Consumer Protection. From the results of the study, it can be concluded that legal protection of brand rights has been regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The law explains that brands will get their rights to obtain protection and legal certainty on the condition that the brand must be registered first. If an irresponsible party is found using another person's brand without the knowledge and permission of the original owner of the brand, then this is included in brand imitation. The parties who do this can be threatened with criminal or civil charges.